Perceived Quality, Trust, Satisfaction on Student Loyalty in Private Universities - Elistia Elistia; Jovita Nathania; Rojuaniah; Lista Meria; Mitsalina Tantri (Journal of Business and Behavioural Entrepreneurship, 2022)
The best universities certainly have advantages which are their competitiveness. These are essential studies conducted at private universities in West Jakarta, Indonesia, about the effect of perceived quality, trust, and student satisfaction on student loyalty. This study aims to examine the effect of perceived quality on students, student satisfaction, and student confidence in student loyalty. The population of this research is the five best universities in West Jakarta, with a total sample of 150 students. The research design used in this study is a causal descriptive research design and uses a quantitative method approach that is processed and tested using SEM-PLS. The findings of this study indicate that the perceived quality of students, student trust, and student satisfaction is proven to increase student loyalty, and the perceived quality of students will affect student loyalty through student satisfaction. These findings have also provided a better understanding of how each factor affects student loyalty. This research contributes to the theoretical and practical levels, as well as contribute knowledge to the determinants of student loyalty at the 5 Best Private Universities in West Jakarta, Indonesia.